PENGEMBANGAN MODEL PEMBELAJARAN IPS DENGAN PENDEKATAN KONSTRUKTIVISME DI SEKOLAH (Faculty of Social Science, Universitas Negeri Semarang, 2014)
Social science plays an important roles in the development ofIndonesian educational system. It supports the students to gain the competency of well human being and citizenship.The reconstruction of the curriculum for several times makes the teacher of social science studiesthink an alternative methodology of teaching. This alternative methodology shoul be constructive and critical. To stimulate the students learning interest, they are needed to be brought closer to the social issues around their environtment. It is expected to construct their critical awareness to their communities. They are not longer dominated by the teacher in the learning process. The teacher just provides the discourse and facilitates them to have some critical pedagogy activities.The aim of this article is togive an overview of Social Science learning process based on theconstructivism model. This theory supports a critical pedagogydevelopment which brings the students become a good critically and responsibility citizen. Education , Social Studies, Constructivism , School